Análise do armazenamento e preservação do acervo em microfilme no Arquivo Público do Estado do Pará - VELASCO, Pâmela Gonçalves (2022)
Analysis of storage and preservation techniques of Pará's State Public Archive microfilmed collection. The analyzed collection belongs to "Secretaria da capitania" that owns documents made by authorities from Portugal Kingdom and Brazilian captaincies of captaincies the colonial period. This research's purpose is to analyze the microfilmed document preservation techniques with qualitative descriptive research from case studies and field research. It was discussed the importance of microfilming historical documents, its legal aspects and the reasons for the paper based documents not being microfilmed anymore at Pará's State Public Archive. Throughout this research it was verified that the documents and microfilms were preserved although there were not equipments for the reproduction of the microfilms. The organization is looking to address this issue.